Integrating Local Wisdom Through the Hedung Huriq Dance as a Learning Resource For Social Studies And Civics In Elementary Schools - Victor Novianto; Sulaiman; Selly Rahmawati (UM Purwokerto Press, 2025)
This study investigates the integration of local wisdom embedded in the Hedung Huriq dance as a pedagogical resource for Social Studies (IPS) and Civic Education (PKn) in elementary schools. The research positions Hedung Huriq not only as a cultural performance but as a repository of historical memory, social norms, and civic values that are vital for character learning. Using a qualitative descriptive method, data were collected through interviews with cultural leaders and teachers, direct observations of symbolic dance movements, and document analysis. The findings show that Hedung Huriq encapsulates values of cooperation, discipline, responsibility, respect for ancestral customs, conflict resolution, and cultural identity formation. These values align with IPS competencies related to cultural understanding, social interaction, and historical reasoning, as well as PKn competencies concerning democratic values, social responsibility, and national identity. The study proposes an ethnopedagogical integration model that includes curriculum alignment, project-based cultural inquiry, reflective learning cycles, and collaboration with local cultural actors. The model demonstrates how traditional arts can foster motivation, deepen cultural awareness, and strengthen civic character. This research contributes to the limited literature on dance-based ethnopedagogy and offers a context-specific framework for embedding local wisdom into elementary-school learning.